MOTIF DAN PENEMPATAN UKIRAN MINANGKABAU PADA HOTEL PUSAKO DI BUKITTINGGI - TASHA REGITA PRAMESTI; Eliya Pebriyeni (Serupa The Journal of Art Education, 2020)
This research aims to find out what carving motif in Hotel Pusako, Bukittinggi, West Sumatera, To know where the placement of the carving motif at Hotel Pusako, Bukittinggi, West Sumatera, To find out how the placement of the carving motifs on Hotel Pusako in view in terms of the placement of carving motifs based on customary provisions.This type of research is qualitative ethnography. This study was conducted by observing/descending into the field, interviews and research in the form of photographs. To analyze the data is done by 1) observation, 2) development findings, 3) interviews, 4) processing of data sources, findings and data analysis, 5) conclusion. Testing the validity of data is done using data triangulation techniques. The results of the research in the conclusion that the carving motifs in the Hotel Pusako is a motif that is in the Rumah Gadang, and the placement is not adjusted to the one in the Rumah Gadang.Kata kunci : Motif Ukiran, Minangkabau, Hotel Pusako, Ketentuan, Rumah Gadang